DC bias electric field effects on ac electrical conductivity of MAPbI3suggesting intrinsic changes on structure and charge carrier dynamics - Minussi, F. B. [UNESP]; Reis, S. P. [UNESP]; Araújo, E. B. [UNESP] (IOP Publishing, 2021)
Methylammonium lead iodide (MAPbI3) emerges as a promising halide perovskite material for the next generation of solar cells due to its high efficiency and flexibility in material growth. Despite intensive studies of their optical and electronic properties in the past ten years, there are no reports on dc bias electric field effects on conductivity in a wide temperature range. In this work, we report the combined effects of frequency, temperature, and dc bias electric field on the ac conductivity of MAPbI3. We found that the results of dc bias electric fields are very contrasting in the tetragonal and cubic phases. In the tetragonal phase, sufficiently high dc bias electric fields induce a conductivity peak appearance ~290 K well evidenced at frequencies higher than 100 kHz. Excluding possible degradation and extrinsic factors, we propose that this peak suggests a ferroelectric-like transition. In the absence of a dc bias electric field, the ac conductivity in the tetragonal phase increases with temperature while decreases with temperature in the cubic phase. Also, ac activation energies for tetragonal and cubic phases were found to be inversely and directly proportional to the dc bias electric field, respectively. This behavior was attributed to the ionic conduction, possibly of MA+ and I- ions, for the tetragonal phase. As for the cubic phase, the ac conduction dynamics appear to be metallic-like, which seems to change to a polaronic-controlled charge transport to increased dc bias electric fields.
Keywords: ac conductivity; ferroelectric; halide perovskites; ionic and polaronic charge carriers